2021
DOI: 10.1055/s-0041-1722956
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Computational Fluid Dynamics Preoperative Analysis of the Nasal Airway

Abstract: Evaluation of the nasal airway is crucial for every patient with symptoms of nasal obstruction as well as for every patient with other nasal symptoms. This assessment of the nasal airway comprises clinical examination together with imaging studies, with the correlation between findings of this evaluation and symptoms reported by the patient being based on the experience of the surgeon. Measuring nasal airway resistance or nasal airflow can provide additional data regarding the nasal airway, but the benefit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 116 publications
(206 reference statements)
0
8
0
Order By: Relevance
“…Gender, racial, and ethnic differences in nasal anatomy and function need to be considered as well [ 22 ]. Another limit of the study is that our CFD model does not take account of some parameters which play a role in respiratory dynamics, such as heat transfer from the air to the nasal mucosa, wall shear stress, airstream velocity, and streamlines [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gender, racial, and ethnic differences in nasal anatomy and function need to be considered as well [ 22 ]. Another limit of the study is that our CFD model does not take account of some parameters which play a role in respiratory dynamics, such as heat transfer from the air to the nasal mucosa, wall shear stress, airstream velocity, and streamlines [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…18,19 In recent years, CFD has become an important tool in the field of biomedical research, such as the analysis of blood flow in the blood vessel [20][21][22] and gas flow in the respiratory system. 23,24 The numerical model can be used for theoretical simulation of some physical conditions and numerical study of parameters after experimental validation. 24 Gao et al 25 concluded that CFD based on the SST K-ω turbulence model could be used as a research platform for root canal irrigation through in vitro irrigation model validation.…”
Section: The Development Of Root Canal Irrigation Research Methodsmentioning
confidence: 99%
“…CFD was first applied in the field of engineering 18,19 . In recent years, CFD has become an important tool in the field of biomedical research, such as the analysis of blood flow in the blood vessel 20–22 and gas flow in the respiratory system 23,24 …”
Section: The Development Of Root Canal Irrigation Research Methodsmentioning
confidence: 99%
“…Therefore, it can be seen as an effective way to study airflow in nasal cavity. 9 Many scholars have developed models of the upper airway and performed finite element analyses. Zhao et al 10 studied the upper airway after maxillary skeletal expansion treatment by CFD, and suggested that Maxillary Skeletal Expansion appliance may show positive effects in the improvement of upper airway cross-sectional areas and reduction of upper airway resistance and velocity.…”
mentioning
confidence: 99%
“…Recently, CFD has been used as a noninvasive method to simulate flow behavior. Therefore, it can be seen as an effective way to study airflow in nasal cavity 9 . Many scholars have developed models of the upper airway and performed finite element analyses.…”
mentioning
confidence: 99%